"Lock This Whore Up": Legal Violence and Flows of Information Precipitating Personal Violence against People Criminalised for HIV-Related Crimes in Canada. (6th May 2019) - MCCLELLAND, Alexander
Abstract : This article examines the convergence of myriad forms of information on people who come to be targets of state and public control due to the perceived risk they present through having been alleged to have not disclosed their HIV-positive status to sex partners. Attending to the material, violent impacts of criminalisation – violence, both legal and extralegal – this article outlines how punishment is enhanced and amplified through the flow of information. Focusing on the material impacts of flows of information about the daily lives of people who face criminalisation moves analysis beyond solely a theoretical object of inquiry and helps to frame an understand that the effects of big data operate not just "within" big data surveillance, but also "beyond" big data surveillance.